Effects of Government's Policy in Stock Price: A Case of Nepse - Ganesh Prasad Niraula (Universitas Negeri Gorontalo, 2022)
The purpose of this study is to find out the relationship of government's policy on the price movement of Nepal stock exchange (NEPSE). This study followed a case study research design, because it offers a deeper perspective and clearer understanding of the stock price movement of Nepalese joint venture banks. The sample size of this study consists of five joint venture commercial Banks, economic analysis and survey reports conducted by central bank of Nepal (Nepal Rastra Bank).The judgmental sampling method has been applied for selection of joint venture banks. The study was totally based on secondary data. in order to make proper analysis descriptive and inferential statistics were used using SPSS software version 26. The finding of this study revealed that the GDP and import are inversely associated with stock price movement and CRR, export, interest rate and inflation are positively associated with stock price movement. Further, it is found that the macroeconomic variables are key factors to determine the Nepalese stock price movement. More importantly, stock market has been found to respond significantly to changes in the government policy. It is recommended that CRR, EXPORT, INTEREST RATE and INFLATION are major factors which largely affect the stock price movement of NEPSE. GDP and IMPORT are not compliance with the stock price movement as they produce negative association with the stocks volatility.